PENINGKATAN HASIL BELAJAR IPA KELAS IV SD DENGAN MODEL EXAMPLE NON EXAMPLE - Restio Sidebang (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to improve the students’ learning outcomes by using examples non examples learning model on science subjects in class IV. The subjects of this research were all fourth graders of Private Primary School Advent Sumbul. The object of this research is the use of examples non examples model to improve the students’ learning outcomes on science subjects. Methods of data collection was through tests, observations, and documentation. Data analysis used comparative analysis. Based on the research shows that there is an increase of activity and learning outcome of IPA through example non examples model seen from the first cycle that is on the observation of teacher activity percentage 58,88% which enough category, 44,44% students’ activity, classical mastery 42,42% with average 70. The results of the second cycle is teacher activity of 67,70%, 73,33 students’ activity, 90,1% classical completeness. Based on the data analysis of the classroom students’ learning result increased by 15,46%.